Improving Students' Academic Writing Skills Through Metacognitive Strategies - Nusivera, Egi; Hikmat, Ade; A. Ghani, Abdul Rahman (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
The purpose of this study was to investigate the effectiveness of metacognitive writing strategies in enhancing academic writing skills among college students. A total of 150 college students in West Java, Indonesia, participated in this study. The method used in this study was factorial design analysis. Confirmatory factor analysis was used to answer the problem formulation. The data collection instruments used were a metacognitive writing strategy questionnaire and an academic writing test with several topics. The results of the study showed that the questionnaire instrument for assessing the use of metacognitive strategies in the writing process was proven valid, as it effectively measured students' metacognitive awareness. Second, metacognitive strategies significantly contributed to students' academic writing skills. Metacognitive strategies act as high-level constructs, and a positive correlation was found between the dimensions of metacognitive strategies. The dimensions of metacognition that were found to be correlated and contributed to each other were declarative, procedural, conditional, planning, monitoring, evaluation, information management, and debugging strategies. From the comparison of the proposed models, the second model (eight-component correlation model) is more effective in contributing to academic writing skills than the first model, as it describes all the contributing components significantly more comprehensively. The study suggests that academic writing skills can be enhanced by increasing students' metacognitive awareness and reflective abilities regarding their writing process.